Inflammatory, Oxidative Stress, and Angiogenic Growth Factor Responses to Repeated-Sprint Exercise in Hypoxia - Kasai, Nobukazu; Kojima, Chihiro; Sumi, Daichi; Ikutomo, Akiho; Goto, Kazushige (Frontiers in Physiology, 2019)
The present study was designed to determine the effects of repeated-sprint exercise in moderate hypoxia on inflammatory, muscle damage, oxidative stress, and angiogenic growth factor responses among athletes. Ten male college track and field sprinters [mean ± standard error (SE): age, 20.9 ± 0.1 years; height, 175.7 ± 1.9 cm; body weight, 67.3 ± 2.0 kg] performed two exercise trials in either hypoxia [HYPO; fraction of inspired oxygen (FiO2), 14.5%] or normoxia (NOR; FiO2, 20.9%). The exercise consisted of three sets of 5 s × 6 s maximal sprints with 30 s rest periods between sprints and 10 min rest periods between sets. After completing the exercise, subjects remained in the chamber for 3 h under the prescribed oxygen concentration (hypoxia or normoxia). The average power output during exercise did not differ significantly between trials (p = 0.17). Blood lactate concentrations after exercise were significantly higher in the HYPO trial than in the NOR trial (p < 0.05). Plasma interleukin-6 concentrations increased significantly after exercise (p < 0.01), but there was no significant difference between the two trials (p = 0.07). Post-exercise plasma interleukin-1 receptor antagonist, serum myoglobin, serum lipid peroxidation, plasma vascular endothelial growth factor (VEGF), and urine 8-hydroxydeoxyguanosine concentrations did not differ significantly between the two trials (p > 0.05). In conclusion, exercise-induced inflammatory, muscle damage, oxidative stress, and VEGF responses following repeated-sprint exercise were not different between hypoxia and normoxia.